PENERAPAN TOTAL QUALITY MANAGEMENT ( TQM ) UNTUK PENGENDALIAN TOTAL KUALITAS DALAM GUDANG LOGISTIK BERAS BULOG DI KOTA SORONG - MAHMUD, FADILA MAHMUD; Gani, Mardhiah; Muliati, Zulfa; Hahury, Sanny; Tajuddin, Tamrin (Industrial Engineering Journal – System, 2024)
This research aims to find research gaps by using Publish or Perish (Pop) to obtain data from the Google Scholar website and visualize it via Vosviewer software with the results of developments in research topics and issues centered on "Total Quality Management" for total quality control in Bulog rice warehouses. Based on mapping the distribution of publications, there are 255 journals regarding 5 keywords. Journal publication on the Vosviewer bibliometic study, thus showing the results of network visualization of keywords containing 7 clusters and 37 items. The implication and contribution of this research is mapping the research topic on Total Quality Management on quality control in Bulog rice logistics warehouses which are often or even very rarely researched by researchers, so it is recommended for future researchers to use as a basis or reference.